The Effect of Using Marathon Shoes or Track Spikes on Neuromuscular Fatigue caused by a Long-distance Track Training Session - Ruiz-Alias, Santiago A.; Pérez-Castilla, Alejandro; Soto-Hermoso, Víctor M; García-Pinillos, Felipe (International Journal of Sports Medicine, 2023)
This study aims to compare the effect of the Nike ZoomX Dragonfly track spikes and the Nike ZoomX VaporflyNext% 2 marathon shoes on the fatigue manifestations present over and after a long-distance track training session. Thirteen highly trained athletes completed two training sessions (i. e., 9- and 3-minute time trials with complete recovery) with the aforementioned footwear models. The pace, ground contact time, and stride length were measured over the time trials, and maximal countermovement jumps were performed previously and after the training session. The results revealed that, although there was no significant interaction in the pace distribution (p≥0.072), athletes tend to be only able to increase the pace at the last lap with the marathon shoes (5.4 meters [−3.7 to 14.5 meters]) meanwhile with the track spikes it further decreased (−3.1 meters [−9.8 to 3.6 meters]). A reduced ground contact time over the session (p=0.025) and a tendency toward increasing stride length (p=0.09) in the last time trial were observed. The significant interaction on the countermovement jump height (p=0.023; Track spikes: −5.60%; Marathon shoes: 0.61%) also indicates that footwear influences the resulted allostatic load.
Keywords: running performance; training; fatigue